Fluorosis in Vallioor Union of Tirunelveli District, Tamilnadu, India - Santhi, D.; Umayoru Bhagan, V.; Lekshmana Sarma, R. (Asian Journal of Chemistry, 2010)
Abnormal level of fluoride in ground water causes serious health hazards in human beings. The excessive intake of fluoride ion beyond the prescribed limit leads to dental and skeletal fluorosis, Fluorosis is a well defined clinical entity caused by ingesting excessive amount of fluoride, characterised by dental mottling, skeletal and other non-skeletal manifestations. This study reveals the fact that occurrence of fluoride is highly sporadic and localized in southern part of Vallioor Union of Tirunelveli District and the concentration of fluoride varies from 1.45 ppm to 5.37 ppm and it also shows the percentage of people affected by fluorosis.